Model reduction of discrete interval system using clustering of poles. (4th September 2012) - Singh, V.P.; Chandra, D.
This paper presents a method for reduction of discrete interval systems using pole clustering and Padé approximation. For a given high-order system, denominator of the reduced-order model is obtained by pole clustering and the numerator is obtained by matching first r time moments of the system and its reduced-order model where r is the order of reduced-order model. Two numerical examples are included to illustrate the procedure.